2018
DOI: 10.3389/feart.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Role of Terrestrially Derived Humic Substances in the Marine Biogeochemistry of Iron

Abstract: There is a widely recognized link between iron bioavailability and phytoplankton growth in large tracts of the World Ocean. Iron bioavailability is thus pivotal to the removal of atmospheric carbon via the ocean's 'biological pump.' To evaluate future scenarios of global climate change, we must therefore understand better how the bioavailability of iron in seawater is linked to processes controlling its supply, chemical speciation and removal from the water column. Much of the research on iron inputs to the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 179 publications
(295 reference statements)
1
30
0
1
Order By: Relevance
“…Fe transport capacity varied from 0.7 % to 24 % among the rivers. The high Fe transport capacity for most of the rivers studied go along with the existing literature showing that high-latitude DOC-rich rivers exhibit higher Fe-carrying capacities (Krachler et al, 2005;Muller, 2018). DOC was little affected by increasing salinity, as previously observed in high-latitude rivers with high DOC concentrations (Herzog et al, 2017;Forsgren et al, 1996).…”
Section: Fe Transport Capacity and The Link To Fe Speciationsupporting
confidence: 77%
“…Fe transport capacity varied from 0.7 % to 24 % among the rivers. The high Fe transport capacity for most of the rivers studied go along with the existing literature showing that high-latitude DOC-rich rivers exhibit higher Fe-carrying capacities (Krachler et al, 2005;Muller, 2018). DOC was little affected by increasing salinity, as previously observed in high-latitude rivers with high DOC concentrations (Herzog et al, 2017;Forsgren et al, 1996).…”
Section: Fe Transport Capacity and The Link To Fe Speciationsupporting
confidence: 77%
“…The SRFA standard solution was saturated with Fe prior to use to ensure the voltammetric signal reflected the contribution of all Fe-binding groups (Sukekava et al 2018). Previous work (Laglera and van den Berg 2009) has shown that the binding capacity of SRFA is 16.7 nM Fe/mg FA. We used this value as a guide to saturate the SRFA standard.…”
Section: Adsorptive Cathodic Stripping Voltammetrymentioning
confidence: 89%
“…Assuming a ratio of 16.7 nmol Fe (mg FA) −1 for the binding capacity of humic substances (Laglera and van den Berg 2009), the maximum concentration of Fe-binding by humic substances would have been 0.2-5.8 nmol L −1 (Table 3). Based on previous studies, most of dissolved Fe would have been anticipated to occur as organic complexes, mainly with humic substances (Laglera and van den Berg 2009). In reality, the binding capacity of humic substances could only explain a maximum of between 0.2% and 13% (median is 2%) of the dissolved Fe (0.22 μm) ( Table 3).…”
Section: Size-fractionated Fe Proportion and Fe-binding By Humic Subsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, with regard to the truly dissolved Fe fraction (typically a much lower concentration than the solid Fe phase), found it behaved conservatively in the Ob and Yenisey estuaries. Some dissolved and colloidal Fe-binding constituents of aquatic humic substances also appear not to be subject to coagulation along the estuarine salinity gradient (Merschel et al 2017;Muller 2018). Hence, although it seems likely much particulate Fe is deposited to estuarine sediments, a portion can still be transported through estuaries to the coastal ocean (Sanders et al 2015).…”
Section: Metal Behaviour During Estuarine Mixingmentioning
confidence: 99%